GELOMBANG PANAS LAUT - Dewi Surinati (OSEANA, 2021)
The hot temperature on Earth and ocean dynamics processes could cause the phenomenon of a heatwave. Besides land, heatwaves could occur in the ocean, known as marine heatwaves (MHWs). Understanding the MHWs is important because of their huge impact on marine life and humans. Therefore, it is hoped that we can protect vulnerable marine habitats and resources by increasing general awareness of this phenomenon, and by increasing our scientific understanding of its physical properties and ecological impacts.